Oral Cavity Metastasis of Hepatocellular Carcinoma following Liver Transplantation. (4th October 2012) - Goldaracena, Nicolás; Barreto, Mariela; Casas, Gabriel; Anders, Margarita; Mastai, Ricardo; McCormack, Lucas
Abstract : Liver transplantation (LT) remains the only cure for hepatocellular carcinoma (HCC) in many cases. Over many years, most centers have applied the Milan criteria for selecting cirrhotic patients with HCC for LT. In a new era where several transplant groups are pushing the limits of transplanting HCC outside Milan criteria as an aggressive approach with promising results, we present interesting images of a patient that presented a unique and rare site of HCC metastasis after 36 months of liver transplantation.